Prioritizing failures by using hybrid multi criteria decision making methodology with a real case application - Erdogan, Melike; Kaya, Ihsan (ELSEVIER, 2019)
Development of a sustainable public transportation network is one of the most important factors for establishing a sustainable city. Failure analysis for public transport systems is not an issue to be adequately addressed. However, this issue has great importance in terms of maintenance planning and reliability. So, this paper aims for prioritizing failures for corrective actions in Bus Rapid Transit System (BRT) by using a hybrid Multi Criteria Decision Making (MCDM) methodology. In this paper, a prioritization analysis is carried out by using a hybrid mechanism consists of stochastic, fuzzy approaches and Delphi Method for failure with uncertainties. The proposed hybrid MCDM methodology has been applied for the BRT system in Istanbul, Turkey. Both fuzzy and stochastic approaches have been applied to deal with all the uncertainty in the process. To model uncertainties discussed in fuzzy logic more precisely, type-2 fuzzy analytic hierarchy process (AHP) method has been used to determine the weights of the criteria for failures. After the criteria's weights are clarified, a stochastic TOPSIS method is adopted for obtaining the ranking of the failures in the better model of the probabilistic uncertainty. At all these stages, Delphi method also has been applied to obtain experts' evaluations. These evaluations are used as input for the proposed MCDM methodology. Finally, identification and ranking the importance of the failures for BRT system have been clarified. So that it is aimed to support decision makers in taking the maintenance decisions of the vehicles by using the proposed approach.
Keywords: BRT; Failures; Multi criteria decision making; Type-2 fuzzy sets; AHP; Stochastic TOPSIS; ANALYTIC HIERARCHY PROCESS; ENERGY ALTERNATIVES; VIKOR METHOD; MODEL; SELECTION; UNCERTAINTY; FRAMEWORK; SUSTAINABILITY; JUDGMENTS; Construction & Building Technology; Science & Technology - Other Topics; Energy & Fuels